High-resolution phosphorus transfers at the catchment scale: the hidden importance of non-storm transfers - P. Jordan; J. Arnscheidt; H. McGrogan; S. McCormick; S. McCormick (Hydrology and Earth System Sciences, 2005)
High-resolution measurements of total phosphorus (TP) concentrations in a stream draining a 5 km2 agricultural catchment (a sub-catchment of Lough Neagh in Northern Ireland) were made every 10 min by continuous flow instrumentation using new homogenisation, digestion and colorimetric phases. Concurrently, rainfall and stream discharge data were collected at 5 and 15 min intervals. Major P flushing episodes during storm events peaked on the rising limbs of storm hydrographs. A period of baseflow also indicated the importance of other sources that maintain the stream in a eutrophic state between storm events. These data provide insights into catchment processes that conform to definite patterns that, in a coarser sampling regime, might ordinarily be attributed to sampling and analytical 'noise'.